Avaliação da qualidade dos serviços prestados pela secretaria de cursos unificada da Universidade Federal de Mato Grosso no campus Araguaia - Teixeira, Maria de Fátima Freitas Oliveira (2024)
The topic of service quality is widely discussed in the literature due to its relevance. Many studies focus on seeking concepts and developing different models for evaluating service quality in various contexts. In the field of public services, quality assessment faces challenges such as limited resources. At public universities, government policies and regulations act as independent variables influencing various aspects of management. Higher education institutions, as public service entities, have the responsibility to meet societal demands. Therefore, it becomes essential to evaluate the services provided. Thus, this study aims to evaluate the quality of services offered through the perceptions of users of the unified course secretary (SCU) at the Federal University of Mato Grosso (UFMT) in the Araguaia Campus (CUA). This study was structured following the format of a collection of articles, with the results divided into two stages, utilizing a combined quantitative and qualitative approach. The first article consists of a systematic literature review (SLR) whose general objective was to analyze scientific research on measuring service quality in public universities, mainly in administrative service sectors. After selecting 84 relevant articles, it was found that the United States is the country with the highest number of publications on the topic. The main keywords identified were "service quality" and "higher education." The second article consists of research that used the case study method through the SERVPERF questionnaire, document observation, and semi-structured interviews. The general objective of the work is to evaluate the level of service quality based on the five dimensions of quality: Tangibility, Reliability, Responsiveness, Assurance, and Empathy. The target audience included course coordinators, faculty, and students, totaling 264 completed questionnaires. In addition, 23 interviews were conducted, 16 of which were with course coordinators and seven with professors. Data analysis was conducted through a combined quantitative and qualitative approach. In the quantitative analysis, using descriptive statistics, it was observed that the lowest average was found in the responsiveness dimension, according to the perception of students. Regarding the perceptions of course coordinators and professors, the dimension with the lowest average was tangibility, followed by the responsiveness dimension. However, the dimension with the highest average was assurance, both for coordinators, faculty, and students. Therefore, there is a significant need for improvements in services related to the dimensions of responsiveness and tangibility. In the qualitative analysis, content analyses were conducted where service users expressed dissatisfaction in certain aspects, mainly in the tangibility and responsiveness dimensions. Although praises were noted, shortcomings in meeting the needs of coordinators and faculty were also highlighted. The main suggestions for improvement include defining a more suitable location for the SCU and conducting training courses for sector staff. Limitations and perspectives for future research are also discussed at the end of this study.